Search for Bc+ decays to the pp[bar]π+ final state - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physics letters, 2016)
A search for the decays of the Bc+ meson to pp¯π+ is performed for the first time using a data sample corresponding to an integrated luminosity of 3.0 fb−1 collected by the LHCb experiment in pp collisions at centre-of-mass energies of 7 and 8 TeV. No signal is found and an upper limit, at 95% confidence level, is set, fcfu×B(Bc+→pp‾π+)<3.6×10−8 in the kinematic region m(pp‾)<2.85 GeV/c2, pT(B)<20 GeV/c and 2.0<y(B)<4.5, where B is the branching fraction and fc (fu) is the fragmentation fraction of the b quark into a Bc+ (B+) meson.